(untitled) (AmeriQuests, 2012)
What is the worth of humanities teaching and research? This collaborative report, based on meetings at McGill and Vanderbilt Universities, argues that humanities researchers and teachers help make an historical, public, meaningful world. It outlines the character of the relationship between the humanities on one side and artistic and political work on the other. It suggests several challenges facing the humanities and provides a short list of recommendations.